Non-medical use, abuse and dependence on prescription opioids among U.S. adults: psychiatric, medical and substance use correlates. - Becker, William C; Sullivan, Lynn E; Tetrault, Jeanette M; Desai, Rani A; Fiellin, David A (Drug and alcohol dependence, 2008)
Non-medical use of prescription opioids carries risks including development of abuse/dependence. Such use may correlate with psychiatric, medical, and substance use characteristics.
Keywords: Adolescent; Adult; Agoraphobia; Alcohol Drinking; Child; Chronic Disease; Cross-Sectional Studies; Diagnostic and Statistical Manual of Mental Disorders; Drug Prescriptions; Factor Analysis, Statistical; Female; Health Status; Humans; Male; Opioid-Related Disorders; Pain; Panic Disorder; Phobic Disorders; Prevalence; Questionnaires; United States